Memória traumática em amada, de Toni Morrison : interface comparativa entre texto e leitor - Lôbo, Rebecca Luiza de Figueiredo (2023)
The present dissertation aims to understand how literature creates, integrates, and heals trauma from the perspective of Shwab (2000), through the aesthetic recreation of African American traumatic memory in my interaction with Toni Morrison's novel Beloved. To achieve this, I relied on the concepts of Aesthetic Effect Theory and the articulation proposed by Carmen Sevilla Santos (2009) with the Historical-Cultural Theory. In doing so, I establish a dialogue between this articulation and Schwab's perspective that literature functions as a form of cultural contact, in which the author relies on Winnicott's (1975) concept of transitional object. The research method has a metacognitive and metaprocedural nature, as I investigate my own cognitive processes during the reading experience and the procedures involved in this activity through mapping, through which I reflect on the potentials and limitations of the aesthetic experience with African American literature in the elaboration of collective trauma. The results indicate that the structure of the novel has the potential to help break emotional silence about traumatic memory because by presenting the characters' traumatic experiences as voids, it invites the reader to use their imagination to recognize them and, consequently, to engage cognitively and emotionally with the experiences hinted at by the narrative.